(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article examines the concept of mediaocracy and its role in modern political processes. The authors analyze how media organizations and media interests can influence the formation of public opinion, political decisions and elections through the mechanisms of media attention, opinion formation, information control and funding. The article also discusses potential challenges and risks associated with mediacracy and possible measures to ensure balance and transparency in political communication in the information society.